Consumo colaborativo: uma perspectiva por meio do estudo de campanhas sociais nas redes sociais online. - Costa , Lívia Maciel Guimarães (2016)
Debates about the collaborative consumption has gained strength in the current academic studies due to the fact that it is a recent subject, experienced differently by society, such as the Uber app, the Airbnb.com website, the online thrift stores, groups of online ride, the crowdfunding platforms such as Catharsis, among others. However, it was noted that most studies discusses the collaborative consumption in a more restricted way, to understand the consumption as the purchase, exchange or sharing of tangible goods. Although there is a perspective of collaborative consumption which relates to sharing of ideas, this one has the focus, usually in the development of a personal project. Thus, this research sought to understand how the collaborative consumption can be seen from the perspective of society, assisting projects aimed at helping people, such as social campaigns that have been carried out in the virtual environment. So, aimed to examine, in the light of online social networks, the possible relationships between the aid decision procedures to social campaigns and the collaborative consumption. To that end, a research model that describes the steps of the aid decision process was defined, which can be influenced by internal and external factors in order to analyze it from the perspective of social campaigns that are carried out on online social networks as a way of understanding how the collaborative consumption can occur in this process. As a result, the methodological procedures occurred as follows: in data collection were carried out in-depth interviews, qualitative, semi-structured, online through Facebook chat, with 16 people who said they had collaborated, more than once with this kind of campaign. The participants selection was based in friend’s suggestions and information sharing on social networks. To analyze the data, in turn, the content analysis was used. It was found that there are several types of social campaigns that are spread in social networks and that there is more than one way to collaborate with them, highlighting the donation of money that is similar to crowdfunding, donating blood, hair and provisions and sharing the campaign in their own social networking as a way to attract more collaborators. In addition, it was observed that the aid decision-making process regarding such campaigns following the steps outlined in the model, with a few own specifications of the context in which they are held (the virtual environment), being possible to suggest the stage of post collaboration, which occurs when the individual continues to accompany the campaign even after the collaboration.